Identificação in silico de pequenos RNAs não codificantes em genoma de Proteus mirabilis uropatogênico - Rocha, Sérgio Paulo Dejato da (2016)
The urinary tract is a frequent site of infections in both community and admitted to hospitals patients. The urinary tract infection (UTI) is characterized by proliferation of bacteria in any part of the urinary tract: kidney, ureters, bladder or urethra. The urinary tract infection associated with catheter (ITU-CA) is the most common nosocomial infection and represents more than 80% of nosocomial UTI. Proteus mirabilis, a Gram-negative bacterium, is not a common cause of UTI in normal patients, being more related to complicated ITU, especially the ITU-CA. P. mirabilis has dozens of sequenced genomes whose size ranges from 3 to 5 Mb. Small RNAs (sRNAs) are short sequences of RNA that regulate gene expression. These molecules act pairing with the target sequences by specific or partially complementary bases. In prokaryotes the sRNAs play key roles in regulatory networks of expression in response to environmental stimuli, including pathogenic bacteria. The computational approach is considered one of the most efficient for locating new sRNAs. It can be divided according to the search method used; among which may be cited those seeking consensus secondary structures; those who carry out the search for rare transcription signals; and those applying comparative genomics and ab initio. Thus, this work constitutes the identification and characterization of small non-coding RNAs in the genome of P. mirabilis through in silico analysis. The sRNA candidates in the genome of P. mirabilis HI4320 strain were predicted using the INFERNAL/Rfam and nocoRNAc programs. In total 29 were predicted sRNA whose sizes ranged from 41 to 505 nucleotides, averaging 273 nucleotides. Of this total only eight could be characterized. Six has been described in Escherichia coli and two in Lactococcus lactis genomes. Regarding the families, four are cis-reg and four are genes-sRNA and all are located in the bacterial chromosome. Concerning the function, they are all involved in regulating of proteins expression in prokaryotes metabolic pathways. Therefore, these results are unpublished and may contribute to the knowledge of the regulation of gene expression in this uropathogen. For these molecules are not be only predicted a future in vitro experimental validation becomes necessary as well as the search for the targets and understanding of its regulatory functions.